Gemcitabine as chemotherapy of head and neck cancer in Fanconi anemia patients - van Harten, Anne M.; Shah, Ronak; de Boer, D. Vicky; Buijze, Marijke; Kreft, Maaike; Song, Ji-Ying; Zürcher, Lisa M.; Jacobs, Heinz; Brakenhoff, Ruud H. (Oncogenesis (New York, NY), 2024)
Fanconi anemia (FA) is a rare hereditary disease resulting from an inactivating mutation in the FA/BRCA pathway, critical for the effective repair of DNA interstrand crosslinks (ICLs). The disease is characterized by congenital abnormalities, progressing bone marrow failure, and an increased risk of developing malignancies early in life, in particular head and neck squamous cell carcinoma (HNSCC). While ICL-inducing cisplatin combined with radiotherapy is a mainstay of HNSCC treatment, cisplatin is contra-indicated for FA-HNSCC patients. This dilemma necessitates the identification of novel treatment modalities tolerated by FA-HNSCC patients. To identify druggable targets, an siRNA-based genetic screen was previously performed in HNSCC-derived cell lines from FA and non-FA tumor origin. Here, we report that the Ribonucleotide Reductase (RNR) complex, consisting of the RRM1 and RRM2 subunits, was identified as a therapeutic target for both, FA and non-FA HNSCC. While non-FA HNSCC cells responded differentially to RNR depletion, FA-HNSCC cells were consistently found hypersensitive. This insight was confirmed pharmacologically using 2′, 2′-difluoro 2′deoxycytidine (dFdC), also known as gemcitabine, a clinically used nucleotide analog that is a potent inhibitor of the RNR complex. Importantly, while cisplatin exposure displayed severe, long-lasting toxicity on the hematopoietic stem and progenitor compartments in Fancg−/− mice, gemcitabine was well tolerated and had only a mild, transient impact. Taken together, our data implicate that gemcitabine-based chemoradiotherapy could serve as an alternative HNSCC treatment in Fanconi patients, and deserves clinical testing.